The Effect of Visual Impairment and Its Severity on Vision-Related and Health-Related Quality of Life in Jordan: A Comparative Cross-Sectional Study - Jammal HM; Khader Y; Kanaan SF; Al-Dwairi R; Mohidat H; Al-Omari R; Alqudah N; Saleh OA; Alshorman H; Al Bdour M (Journal of Multidisciplinary Healthcare, 2023)
Hisham M Jammal,1 Yousef Khader,2 Saddam F Kanaan,3 Rami Al-Dwairi,1 Hasan Mohidat,1 Rami Al-Omari,4 Noor Alqudah,1 Omar A Saleh,1 Haneen Alshorman,1 Muawyah Al Bdour5 1Department of Ophthalmology, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Public Health, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Rehabilitation Science, College of Health Sciences, QU Health, Qatar University, Doha, Qatar; 4Department of Ophthalmology, Faculty of Medicine, Yarmouk University, Irbid, Jordan; 5Department of Ophthalmology, School of Medicine, The University of Jordan, Amman, JordanCorrespondence: Hisham M Jammal, Department of Ophthalmology, Faculty of Medicine, Jordan University of Science and Technology, PO Box 3030, Irbid, 22110, Jordan, Tel +962-2-7201000, Fax + 962-2-7095123, Email hmjammal@just.edu.joPurpose: To assess the effect of visual impairment (VI), its severity, and ocular diseases on vision-related and health-related quality of life (QoL) in Jordan.Patients and Methods: A comparative, cross-sectional, hospital-based study was conducted among a group of 278 patients with VI aged ≥ 18 years, and age and sex-matched control group of 278 individuals with no VI. An interviewer administered the National Eye Institute Visual Function Questionnaire (NEI VFQ-25) and the Medical Outcomes Study 12-Item Short Form Health Survey (SF-12) to all participants.Results: All the mean VFQ-25 subscales scores, physical component scale (PCS) and the mental component scale (MCS) of the SF-12 were significantly lower in patients with VI compared to controls with no VI. The VFQ-25 subscales (except general health and ocular pain), PCS, and MCS scores significantly decreased with more severity of VI. In the adjusted multivariate analysis, lower level of education (p=0.013), male sex (p=0.016), and the presence of cerebrovascular disease (p=0.019) were significantly associated with lower VFQ-25 composite scores in visually impaired patients compared to controls. Ocular disease duration of > 5 years and progressive VI were significantly associated with lower VFQ-25 composite scores (p= 0.026 and p< 0.001) respectively, in patients with VI. Glaucoma had a significantly larger reduction in mean scores of all the VFQ-25 subscales, and the PCS of the SF-12 compared to all other ocular diseases.Conclusion: Both VI and increasing severity of impairment were associated with reduced vision-related and health-related quality of life in adult Jordanians. Glaucoma patients and less educated people were particularly affected. Routine assessment of QoL in visually impaired patients and improving referral protocols to vision rehabilitation services is recommended to improve the QoL in those patients.Keywords: quality of life, SF-12, VFQ-25, vision impairment, vision rehabilitation